Analisis Kualitas Laba Pada Perusahaan Perbankan Syariah di Bursa Efek Indonesia Periode 2016-2020 - wali, Bunga; Mandasari, Nur Fitriayu; Azis, Akbar; Ayuandiani, Wulan; Syahrir, Nurwahyuni; Syahadat, Edy Fitriawan; Puspita, Chandra Putra (Jurnal Manarang Manajemen dan Bisnis, 2023)
This study aims to analyze the quality of earnings in Islamic banking companies whether they have maximum earnings quality. The location of this research wa carried out at the Indonesia Stock Exchange through media browsing on the https://www.idx.co.id website for 10 Islamic banking companies. The sampling technique uses a saturated sampling technique in which the entire population is sampled. The data source is taken fromsecondary data. The data analysis technique uses the earnings quality formula, namely operating profit and average cash to analyze finansial from 2016-2020. The results of the study show that (1) Companies that have good earnings quality are Bank BNI Syariah, Bank Mandiri Syariah and Bank BCA Syariah because they have maximum profit quality. (2) Companies that have poor earnings quality are Bank Muamalat Syariah, Bank Mega Syariah and Bank Jabar Banten Syariah, the rest are considered to have constant earnings quality